Method for extracting vanadium from vanadium slag by chemical etching
The silicate phase of the vanadium slag is selectively destroyed by hydrochloric acid etchant, and the spinel phase is fully exposed, which solves the problems of long oxidation and roasting time, low vanadium leaching rate, and high sulfur content in the existing industrial vanadium extraction technology, achieving high efficiency and low cost vanadium extraction effect.
Patent Information
- Application Number
- CN202510042665.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-04
AI Technical Summary
The existing industrial vanadium extraction technology has problems such as long oxidation and roasting time, low vanadium leaching rate, and high sulfur content of tailings.
Hydrochloric acid is used as an etchant to selectively destroy the silicate phase of the vanadium slag, and selective separation between spinel and silicate phase, so as to completely expose the spinel phase, thereby improving the vanadium grade in the vanadium slag.
The vanadium grade of vanadium essence slag is significantly improved through chemical etching, with lower cost and energy consumption, shortened roasting time, increased vanadium leaching rate to more than 93%, and the tailings are free of sulfur and are environmentally friendly.
Smart Images

Figure CN119753371A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of vanadium extraction chemical industry, in particular to a method for extracting vanadium by chemical etching of vanadium slag. Background Art
[0002] Vanadium is a rare strategic resource. The vanadium slag obtained by smelting vanadium-titanium magnetite in blast furnace and converter is the main raw material for vanadium extraction in my country. Industrially produced vanadium slag is mainly composed of spinel phase, silicate phase, pyroxene phase and a small amount of inclusion phase. Among them, vanadium is mainly enriched in the spinel phase, because spinel crystallizes first during the cooling process of vanadium slag, resulting in being wrapped by the silicate phase that crystallizes at a lower temperature. Vanadium slag often needs to be oxidized and roasted to destroy the wrapped silicate phase before the exposed spinel phase can be oxidized and converted into soluble vanadate. The physical composition and vanadium grade of vanadium slag are very important for the efficient and economic extraction of vanadium.
[0003] In the prior art, technicians in this field have conducted a lot of research on how to efficiently extract vanadium from vanadium slag; however, the current process methods all have many insurmountable problems, such as the relatively mature industrial processes such as sodium roasting-water leaching and calcium roasting-acid leaching. The sodium roasting-water leaching process is to directly add sodium salts (such as sodium carbonate, sodium chloride, etc.) to the vanadium slag to convert vanadium into sodium vanadate through oxidative roasting, and water is used as a leaching agent to recover vanadium; however, the sodium roasting-water leaching process causes serious pollution to the environment, and the vanadium extraction rate is greatly affected by the composition of the vanadium slag. Usually, the roasting time is as high as 120 minutes to achieve the oxidative decomposition of silicates and the formation of water-soluble vanadates. For example, calcium roasting-acid leaching is to add calcium salts to the vanadium slag to convert vanadium into calcium vanadate through oxidative roasting, and sulfuric acid is used as a leaching agent to recover vanadium; however, the impurity content of the leaching solution of this process is high, and the high sulfur content of the tailings is difficult to recover. For example, CN202110505582.9 discloses a method for co-extracting vanadium, titanium and chromium from vanadium slag. This method selectively reduces pyroxene and olivine wrapped in spinel and destroys its structure through low-temperature hydrogen reduction-ferric chloride iron removal and low-temperature oxalic acid leaching of vanadium slag, thereby destroying its structure, achieving the dissociation of spinel phase and silicate phase, and fully exposing the spinel phase. The acidity and strong complexing property of oxalic acid are then used to directly leach the vanadium slag at low temperature, destroying the spinel structure, and allowing vanadium, titanium and chromium to complex with oxalate and enter the solution to achieve the co-extraction of vanadium, titanium and chromium. This method utilizes hydrogen reduction to selectively destroy the pyroxene phase and olivine phase to expose the spinel. Therefore, this method has high requirements for the atmosphere and there are problems with the safety of reducing gas. For example, CN201310416429.4 discloses a method for separating vanadium resources from vanadium slag by ultra-gravity, which method includes the following steps: cooling the molten vanadium slag in the temperature range of 1300-1200°C at a cooling rate of less than 2°C / min to obtain heat-treated vanadium slag; centrifugal ultra-gravity separation of the heat-treated vanadium slag. After centrifugal ultra-gravity separation, refined vanadium slag with a vanadium iron spinel grade of 75-90% can be obtained; the vanadium iron spinel refined vanadium slag separated by ultra-gravity in this invention can be directly used as a raw material for wet vanadium extraction, and the tailings can be used as a raw material for cement production, thereby solving the environmental load problem of vanadium slag and realizing the comprehensive utilization of vanadium slag resources; the method proposes to slowly cool the vanadium slag to 1100°C and combine centrifugal ultra-gravity separation of spinel and silicate phases to obtain high-grade vanadium slag; however, the method has the problem of extremely high requirements for centrifugal equipment and is difficult to industrialize. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a method for chemically etching vanadium slag to extract vanadium, so as to solve the problems of the existing industrial vanadium extraction technology such as long oxidation roasting time, low vanadium leaching rate and high sulfur content in tailings.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions: A method for chemically etching vanadium from vanadium slag is characterized by comprising a chemical etching method: using hydrochloric acid as an etchant to selectively destroy the silicate phase of the vanadium slag, thereby achieving selective separation of spinel and silicate phases in the vanadium slag, completely exposing the spinel phase, and thus improving the vanadium grade in the vanadium concentrate slag.
[0006] Furthermore, the chemical etching method is specifically as follows: crushing and grinding the vanadium slag, adding an etchant to mix and react with it, filtering and separating the solid and liquid after the reaction is completed, and drying the solid to obtain high-grade vanadium concentrate; wherein the etchant is hydrochloric acid with a molar concentration of 0.5 to 2.5 mol / L, the etching reaction temperature is 10 to 50 ° C, the etchant and vanadium slag are mixed at a liquid-solid ratio of 8:1 to 20:1 (ml / g), and then solid-liquid separation is performed to obtain vanadium concentrate.
[0007] Furthermore, the main phases of the vanadium slag are spinel, perovskite phase, calcium ferroolitic olivine, dicalcium silicate and a small amount of magnesium aluminum spinel, etc., and the particle size is less than 0.074 mm.
[0008] Furthermore, the vanadium slag chemical etching method of the present invention also includes a magnesium roasting-acid leaching vanadium extraction step or a sodium roasting-water leaching vanadium extraction step, and the magnesium roasting-acid leaching vanadium extraction step or the sodium roasting-water leaching vanadium extraction step can adopt existing technology or conventional methods.
[0009] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention creatively uses hydrochloric acid as an etchant to selectively destroy the silicate phase of the vanadium slag, thereby completely exposing the spinel phase; that is, a simple and mild chemical etching method is used to achieve the selective separation of the spinel and silicate phases in the vanadium slag, and the spinel of the vanadium concentrate slag after solid-liquid separation is completely exposed without being wrapped by the silicate phase, thereby increasing the vanadium grade in the vanadium concentrate slag by more than 70%. The present invention utilizes the selective enrichment of vanadium in the spinel phase, and the etchant only reacts with the silicate phase but not the spinel phase, thereby achieving the purpose of selectively removing the silicate phase and retaining the spinel phase.
[0010] 2. Lower cost and energy consumption. The present invention uses dilute hydrochloric acid to perform chemical etching at room temperature to dissolve silicon, calcium, phosphorus, and a small amount of iron that wrap the vanadium spinel, so that these elements that have a negative impact on vanadium extraction are separated from the vanadium spinel solid phase. At the same time, no heating is required, and the amount of hydrochloric acid used is relatively small; and during subsequent roasting, the chemically etched vanadium slag only needs less roasting agent and 1 / 2 or even less roasting time to achieve efficient extraction of vanadium.
[0011] 3. The present invention further cooperates with the magnesium roasting-acid leaching step of vanadium extraction or the sodium roasting-water leaching step of vanadium extraction, adopts the vanadium-containing leaching solution for vanadium extraction, produces vanadium products, and the leaching tailings can be recycled. No pollutants are generated in the whole vanadium slag vanadium extraction process, which is very environmentally friendly.
[0012] 4. The vanadium concentrate of the present invention uses MgO or sodium carbonate as a roasting additive, and the clinker sulfuric acid or water leaching process can achieve a vanadium leaching rate of more than 93%, and the acid leaching residue does not contain sulfur. The present invention has excellent roasting kinetic conditions, greatly shortens the roasting time and achieves a high vanadium recovery rate; the acid leaching process reduces the leaching acid consumption, and no calcium sulfate is detected in the residue.
[0013] In summary, the present invention fundamentally solves the problems of silicate encapsulation in vanadium slag leading to harsh roasting and leaching conditions, low vanadium leaching rate, and high sulfur content in tailings. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 It is a process flow chart of the present invention; Figure 2 is the XRD spectrum of Example 1 before and after chemical etching of vanadium slag; Figure 3 The microscopic morphology changes of the vanadium slag before and after chemical etching in Example 1; Figure 4 It is the XRD spectrum of the residue of direct magnesium roasting-acid leaching of vanadium slag and magnesium roasting-acid leaching of vanadium concentrate slag in comparative example 1. DETAILED DESCRIPTION
[0015] The specific implementation modes of the present invention are further described in detail below in conjunction with specific examples.
[0016] The numerical ranges in the present invention are understood to also specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any intermediate value in the stated value or stated range and any other stated value or intermediate value in the stated range is also included in the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded in the range.
[0017] Unless otherwise stated, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art described in the present invention are generally understood. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of conflict with any incorporated document, the content of this specification shall prevail. Regarding "comprising", "including", "having", "containing", etc. used herein, they are all open terms, which means including but not limited to.
[0018] Unless otherwise specified, the experimental methods used in the present invention are all conventional methods.
[0019] Unless otherwise specified, the materials, reagents, etc. used in the present invention can be purchased or synthesized by known methods.
[0020] The quantitative tests in the present invention were all repeated three times, and the results were averaged.
[0021] like Figure 1 As shown, the present invention provides a method for chemical etching of vanadium slag, comprising a chemical etching step and a magnesium roasting-acid leaching step for vanadium extraction; in the chemical etching step, hydrochloric acid is used as an etchant to selectively destroy the silicate phase of the vanadium slag, thereby achieving selective separation of the spinel and silicate phases in the vanadium slag, completely exposing the spinel phase, and thus improving the vanadium grade in the vanadium concentrate slag.
[0022] The magnesium roasting-acid leaching vanadium extraction step can adopt existing technology or conventional methods.
[0023] Example 1 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0024] Weigh 3 g of vanadium slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 93%, and the concentration in the vanadium leachate is 12.8 g / L.
[0025] like Figure 2 This is the XRD spectrum of the vanadium slag in Example 1 before and after chemical etching. It can be seen that the main silicates in the vanadium slag are calcium ferroolitic phase and dicalcium silicate phase, which completely disappear after etching, and the diffraction intensity of the spinel phase is enhanced.
[0026] like Figure 3The microscopic morphology changes of vanadium slag before and after chemical etching in Example 1, wherein the upper two figures are backscattered electron images of vanadium slag, and the lower figure is a backscattered electron image of vanadium concentrate slag after etching. It can be seen that the silicate phase of vanadium slag envelops the spinel phase, and only a small part of the spinel is exposed. However, after etching, the silicate phase disappears, and the spinel and perovskite phases are fully exposed. The larger the specific surface area of the spinel, the more conducive it is to the rapid direct oxidation and recovery of the vanadium slag during roasting.
[0027] like Figure 4 It is the XRD spectrum of the residue of direct magnesium calcination-acid leaching of vanadium slag and the residue of magnesium calcination-acid leaching of vanadium concentrate slag in Example 1. It can be seen that a large amount of CaSO4·2H2O is generated by direct roasting and acid leaching of vanadium slag, making the residue difficult to recover, but no CaSO4·2H2O is detected in the magnesium calcination of vanadium concentrate slag after etching, thus avoiding the formation of high-sulfur tailings.
[0028] By comparison, it can be seen that the present invention uses hydrochloric acid as an etchant to selectively destroy the silicate phase of the vanadium slag, thereby completely exposing the spinel phase; using vanadium concentrate slag and MgO as a roasting additive, the clinker sulfuric acid leaching process can achieve a vanadium leaching rate of 93%, and the acid leaching residue does not contain sulfur; and the acid etchant after each solid-liquid separation is supplemented with a certain amount of fresh hydrochloric acid, which can be recycled multiple times.
[0029] Similarly, the following embodiments can achieve the selective removal of the silicate phase encapsulated in the vanadium concentrate slag, and the spinel phase is completely exposed, thereby fundamentally solving the problems of long roasting and leaching time, low vanadium leaching rate, and high sulfur content in tailings caused by silicate encapsulation in the vanadium slag.
[0030] Example 2 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 2.0 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and leachate were separated. The vanadium concentrate slag (V2O5 content 19.55%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0031] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the molar ratio of magnesium to vanadium of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse three times with deionized water. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 94%, and the concentration in the vanadium leaching solution is 13 g / L.
[0032] Example 3 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.0 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and leachate were separated. The vanadium concentrate slag (V2O5 content 18.15%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0033] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse three times with deionized water. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 90%, and the concentration in the vanadium leaching solution is 11.5 g / L.
[0034] Example 4 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of a 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 50 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 18.89%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0035] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse three times with deionized water. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 92%, and the concentration in the vanadium leaching solution is 12.4 g / L.
[0036] Example 5 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 200 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 ℃ and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and washing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.88%) was dried at 105 ℃ for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0037] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the molar ratio of magnesium to vanadium of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 95%, and the concentration in the vanadium leachate is 13.5 g / L.
[0038] Example 6 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 80 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and washing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.11%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0039] Weigh 3 g of vanadium slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 900°C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40°C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 93%, and the concentration in the vanadium leachate is 12.8 g / L.
[0040] Example 7 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0041] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 650 and 950 ° C for 60 min, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker through 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40 ° C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rates at 650 and 950 ° C are 20% and 82%, respectively, and the concentrations in the vanadium leachate are 2.7 and 11.1 g / L, respectively.
[0042] Example 8 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0043] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the molar ratio of magnesium to vanadium of 1.0 and mix well, place in a muffle furnace and roast at 900 ° C for 10 min and 30 min respectively, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker through 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40 ° C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rates at 10 min and 30 min are 87% and 90%, respectively, and the concentrations in the vanadium leachate are 11.8 and 11.9 g / L, respectively.
[0044] Example 9 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0045] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place in a muffle furnace and roast at 900 ° C for 60 min, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker to 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 2.0 and pH to 4.5 with 20% sulfuric acid, the leaching time is 10 min and the leaching temperature is 40 ° C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rates at pH = 2.0 and pH = 4.5 are 91% and 78%, respectively, and the concentrations in the vanadium leachate are 12.3 and 10.6 g / L, respectively.
[0046] Example 10 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0047] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the molar ratio of magnesium to vanadium of 1.0 and mix well, place in a muffle furnace and roast at 900 ° C for 60 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 2 min and 60 min, and the leaching temperature is 40 ° C; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rates are 85% and 94% at 2 min and 60 min, respectively, and the concentrations in the vanadium leachate are 11.5 and 12.6 g / L, respectively.
[0048] Embodiment 11 The vanadium slag (V2O5 content 11.30%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 19.17%) was dried at 105 °C for 24 h for subsequent magnesium roasting-acid leaching to extract vanadium.
[0049] Weigh 3 g of vanadium concentrate slag with a 200-mesh surface, add MgO according to the molar ratio of magnesium to vanadium of 1.0 and mix well, place in a muffle furnace and roast at 900 ° C for 60 min, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker with 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 3.5 with 20% sulfuric acid, the leaching time is 10 min, and the leaching temperature is 25 and 90 ° C respectively; after the leaching is completed, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rates at 25 and 90 ° C are 87% and 79%, respectively, and the concentrations in the vanadium leachate are 11.9 and 10.8 g / L, respectively.
[0050] Example 12 The vanadium slag (V2O5 content 12.70%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of a 0.5 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and rinsing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 14.75%) was dried at 105 °C for 24 h for subsequent sodium roasting-water leaching of vanadium.
[0051] Weigh 3 g of vanadium slag with a 200-mesh surface, add sodium carbonate according to a sodium-vanadium molar ratio of 3.0 and mix well, place in a muffle furnace and roast at 700°C for 10 min, keep the furnace door slightly open during the process, take out and air cool after the end, and grind the roasted clinker with a 200-mesh surface. Weigh 2 g of clinker and place it in a Mitsui flask, then add 6 mL of deionized water, leaching time is 30 min, leaching temperature is 40°C; after leaching, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 93%, and the concentration in the vanadium leaching solution is 19.7 g / L.
[0052] Example 13 The vanadium slag (V2O5 content 12.70%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.2 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 25 °C and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and washing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 15.10%) was dried at 105 °C for 24 h for subsequent sodium roasting-water leaching of vanadium.
[0053] Weigh 3 g of vanadium slag with a 200-mesh surface, add sodium carbonate according to a sodium-vanadium molar ratio of 3.0 and mix well, place in a muffle furnace and roast at 700°C for 30 minutes, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker with a 200-mesh surface. Weigh 2 g of clinker and place it in a Mitsui flask, then add 6 mL of deionized water, leaching time is 30 min, leaching temperature is 40°C; after leaching, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 95%, and the concentration in the vanadium leaching solution is 20.9 g / L.
[0054] Embodiment 14 The vanadium slag (V2O5 content 12.70%) was crushed and sieved through 200 meshes, 10 g was placed in a three-necked flask, and 100 ml of 1.0 mol / L dilute hydrochloric acid solution was added and placed in a magnetic stirring water bath. The leaching temperature was 10 ℃ and the stirring intensity was 200 r / min. The leaching was carried out for 30 min, followed by vacuum filtration and washing with deionized water three times. The vanadium concentrate slag and the leachate were separated. The vanadium concentrate slag (V2O5 content 14.90%) was dried at 105 ℃ for 24 h for subsequent sodium roasting-water leaching of vanadium.
[0055] Weigh 3 g of vanadium slag with a 200-mesh surface, add sodium carbonate according to a sodium-vanadium molar ratio of 3.0 and mix well, place in a muffle furnace and roast at 700°C for 60 minutes, keep the furnace door slightly open during the period, take out and air cool after the end, and grind the roasted clinker with a 200-mesh surface. Weigh 2 g of clinker and place it in a Mitsui flask, then add 6 mL of deionized water, leaching time is 30 min, leaching temperature is 40°C; after leaching, vacuum filter and rinse with deionized water three times. Separate the residue and vanadium leaching solution, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 96%, and the concentration in the vanadium leaching solution is 20.6 g / L.
[0056] Comparative Example 1 The vanadium slag (V2O5 content 11.30%) was crushed and sieved to 200 mesh and dried at 105℃ for 24 h for direct use in magnesium roasting-acid leaching to extract vanadium. Weigh 3 g of vanadium slag with a 200 mesh, add MgO according to the magnesium-vanadium molar ratio of 1.0 and mix well, place it in a muffle furnace for roasting for 60 min, keep the furnace door slightly open during the period, take it out for air cooling after the end, and grind the roasted clinker to 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 2.5 with 20% sulfuric acid, the leaching time is 30 min and the leaching temperature is 40℃; after the leaching is completed, vacuum filter and rinse three times with deionized water. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 79.7%, and the concentration in the vanadium leachate is 6.7 g / L.
[0057] Comparative Example 2 The vanadium slag (V2O5 content 11.30%) was crushed and sieved to 200 mesh and dried at 105℃ for 24 h for direct use in magnesium roasting-acid leaching to extract vanadium. Weigh 3 g of vanadium slag with a 200 mesh, add MgO according to the magnesium-vanadium molar ratio of 2.0 and mix well, place it in a muffle furnace for roasting for 60 min, keep the furnace door slightly open during the period, take it out for air cooling after the end, and grind the roasted clinker to 200 mesh. Weigh 2 g of clinker and place it in a Mitsui flask, then adjust the leaching pH to 2.5 with 20% sulfuric acid, the leaching time is 30 min and the leaching temperature is 40℃; after the leaching is completed, vacuum filter and rinse three times with deionized water. Separate the residue and vanadium leachate, and adjust the filtrate to 500 ml. According to ICP detection, the vanadium leaching rate is 80.2%, and the concentration in the vanadium leachate is 6.5 g / L.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for extracting vanadium from vanadium slag by chemical etching, characterized in that: The method includes a chemical etching method: using hydrochloric acid as an etchant to selectively destroy the silicate phase of the vanadium slag, thereby achieving selective separation of the spinel and silicate phases in the vanadium slag, completely exposing the spinel phase, and thus improving the vanadium grade in the vanadium concentrate slag.
2. The method for extracting vanadium from vanadium slag by chemical etching according to claim 1, characterized in that: The chemical etching method is specifically: The vanadium slag is crushed and ground, and an etchant is added to mix and react with it. After the reaction is completed, the solid and liquid are separated by suction filtration, and the solid is dried to obtain high-grade vanadium concentrate slag; wherein the etchant is hydrochloric acid with a molar concentration of 0.5 to 2.5 mol / L, the etching reaction temperature is 10 to 50 ° C, the etchant and vanadium slag are mixed at a liquid-solid ratio of 8:1 to 20:1 (ml / g), and then the solid-liquid separation is performed to obtain vanadium concentrate slag.
3. The method for extracting vanadium by chemical etching of vanadium slag according to claim 1 or 2, characterized in that: The main phases of the vanadium slag are spinel, perovskite phase, calcium ferroolitic stone, dicalcium silicate and a small amount of magnesium aluminum spinel, etc., and the particle size is less than 0.074 mm.
4. The method for extracting vanadium from vanadium slag by chemical etching according to claim 3, characterized in that: The method also includes a magnesium roasting-acid leaching step for vanadium extraction or a sodium roasting-water leaching step for vanadium extraction.
5. The method for extracting vanadium from vanadium slag by chemical etching according to claim 4, characterized in that: The steps of magnesium roasting-acid leaching and vanadium extraction are: Magnesium roasting: take the vanadium concentrate obtained in claim 1 or 2, dry it at 105°C for 12 hours, grind it through a 200-mesh sieve, add magnesium oxide and mix well, then roast it at high temperature in a muffle furnace, the amount of magnesium added during roasting is Mg / V=0-3 according to the molar ratio of magnesium to vanadium, the roasting temperature is 650-950°C, and the roasting time is 10-60 min; after roasting, wait for the clinker to cool to room temperature, grind it through a 200-mesh sieve for use; Acid leaching: The clinker obtained after the above roasting is subjected to a sulfuric acid leaching process to obtain a vanadium-containing solution; the roasted clinker is adjusted with 20% sulfuric acid to make the pH of the leaching solution constant at 2.0-4.5 during the leaching process, the leaching temperature is 25-90°C, the leaching time is 2-90 minutes, and the vanadium leaching solution is obtained by leaching.
6. The method for extracting vanadium from vanadium slag by chemical etching according to claim 4, characterized in that: The sodium roasting-water leaching vanadium extraction steps are: Sodium roasting: take the vanadium concentrate obtained in claim 1 or 2, add sodium carbonate and mix well, place in a muffle furnace for high-temperature roasting, the roasting addition amount is based on the sodium-vanadium molar ratio of Na / V=1-3.5, the roasting temperature is 650-850°C, and the roasting time is 10-60min; after the roasting is completed, wait for the clinker to cool to room temperature, grind it through a 200-mesh sieve for standby use; Water leaching: The clinker obtained after the above roasting is placed in a Mitsui flask, and then deionized water is added to carry out a leaching process to obtain a vanadium-containing solution; the leaching temperature is 25-90 ° C, the leaching time is 2-90 min, and after the leaching is completed, vacuum filtration is performed and rinsed three times with deionized water to separate the residue and the vanadium leaching solution.
Citation Information
Patent Citations
A method for separating vanadium resources from vanadium slag using supergravity
CN103451329B
A method for extracting vanadium, titanium, and chromium from vanadium slag
CN113234935B